Curious George - Matthew O'Callaghan; Will, Ferrell; Frank Welker; Drew Barrymore; David Cross; Eugene Levy; Joan Plowright; Dick Van Dyke; Shane Baumel; Tamara Jo Beatty; TimyraJoi Beatty; Christopher Chen; et al. (USA Imagine Entertainment, 2006)
Will Ferrell stars as The Man in the Yellow Hat, a gentleman who looks after his pet monkey - an inquisitive and wonderful creature whose enthusiasm often gets the best of him.
Ted, works as a guide at the Bloomsberry museum, sent on a 'business' trip of sorts by the museum's owner, to find a Zagawa shrine, he encounters a playfully mischievous and curious monkey...actually a chimp who he nicknames 'George' after the George Washinghton statue. His trip being less than a success, he returns stateside, only to find George wanting to return Ted's hat, has stowed away on-board Ted's boat. Back in the states Ted finds himself lumbered with George, who can't help but make Ted's life even more hectic than it already is.
Welcome to the world of Curious George!
Languages : English, German, Dutch, Turkish
Subtitles : English, German, Dutch, Turkish, Romanian, Bulgarian
Keywords: Animation; Adventure; Comedy; Family